Propuesta de Mejora Al Proceso Productivo De Una Empresa Metalmecánica Mediante Herramientas De Lean Manufacturing (2024)
This work is a proposal to improve the production process of a metalworking company using Lean Manufacturing tools. This company is dedicated to the manufacture of gears used in agricultural machinery. An initial diagnosis of the production process is carried out where there are delays and downtime during the process, unnecessary or poorly executed tasks and lack of organization in the environment and cleanliness, so it is decided to use lean tools such as SMED and 5s.